2017
DOI: 10.1016/j.chroma.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive lipidomic analysis of human plasma using multidimensional liquid- and gas-phase separations: Two-dimensional liquid chromatography–mass spectrometry vs. liquid chromatography–trapped-ion-mobility–mass spectrometry

Abstract: Recent advancements in separation science have resulted in the commercialization of multidimensional separation systems that provide higher peak capacities and, hence, enable a more-detailed characterization of complex mixtures. In particular, two powerful analytical tools are increasingly used by analytical scientists, namely online comprehensive two-dimensional liquid chromatography (LC×LC, having a second-dimension separation in the liquid phase) and liquid chromatography-ion mobility-spectrometry (LC-IMS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 92 publications
2
36
0
Order By: Relevance
“…4,6 To date, comprehensive two-dimensional separations are not widely spread in both fields. 25,26 A successful alternative analytical strategy addressed multiple-tailored derivatization methods targeting different chemical moieties thereby covering the whole metabolome while at the same time allowing to resort to a single reversed phase separation. [27][28][29] However, in these studies, lipids are largely omitted.…”
Section: Introductionmentioning
confidence: 99%
“…4,6 To date, comprehensive two-dimensional separations are not widely spread in both fields. 25,26 A successful alternative analytical strategy addressed multiple-tailored derivatization methods targeting different chemical moieties thereby covering the whole metabolome while at the same time allowing to resort to a single reversed phase separation. [27][28][29] However, in these studies, lipids are largely omitted.…”
Section: Introductionmentioning
confidence: 99%
“…evaluated LC-IMS-MS and LC LC-MS-based untargeted lipidomic performances in terms of the number of molecular features, analysis time and structural characterization. From this study, one can see that although a higher number of identified lipids were obtained in LC LC-MS through improving the separation of co-eluting lipids, LC-IMS-MS is overperformed in the faster analysis and accurate lipid identification [ 44 ]. It is recommended to complement the advantages of both techniques for untargeted lipidomics of large-scale complex samples, i.e., conducting comprehensive lipids profiling on the LC LC-MS platform followed by IM-MS for detailed structural characterization [ 44 ].…”
Section: Advances In Analytical Strategies For Mass Spectrometry-basementioning
confidence: 99%
“…Based on previous studies [45,46], the orthogonality of comprehensive 2DLC systems was estimated by a surface coverage method (see ESM). Rather than using several lipid standards [29], all annotated lipids were included in the component pool and used to calculate the coverage metric because the size of analytes in the LC×LC separation really influences the values of orthogonality [47]. To simplify the calculation, several vectors [37] were introduced to compute the effective area of surface coverage which was, as is seen from Fig.…”
Section: Orthogonality and Effective Peak Capacity Estimationmentioning
confidence: 99%
“…To our knowledge, this is the first study on the development and application of 2DLC-MS lipidomics approaches in zebrafish. However, 2DLC-MS lipidomics has been used in other fields such as human plasma [27][28][29][30] and plants [31,32]. The aim of this study was to optimize a variety of LC×LC-MS methods based on C18×HILIC, HILIC×C18, and HILIC×PFP, using the lipid classes found in zebrafish embryos.…”
Section: Introductionmentioning
confidence: 99%